Leadership and Loyalty in Strengthening Civic Engagement - Bakhrawi, Bakhrawi; Pujiati, Heni (Dinasti International Journal of Management Science, 2025)
Leadership, Loyalty and Civic Engagement in the Golkar Party DPP is a shared commitment to realizing democracy in political parties. The aim of this research is to determine and analyze leadership styles and loyalty in strengthening civic engagement using qualitative research. The data collection technique involves conducting interviews with informants who have been selected based on their direct relationship with the Golkar Party DPP. The results of this research are that Leadership in political parties certainly has a dynamic process of selecting the general chairman, especially the Golkar Party DPP, where there is a direct election process by central, provincial and city/district level administrators. Issues related to loyalty will definitely be an internal discussion, where the chairman and administrators must have loyalty to continue fighting for the political and democratic process in this country. Moreover, it is associated with civic engagement (Civic Engagement) which has become a culture within the Golkar Party.